Comparing project-based learning with conventional models: Enhancing students’ enjoyment of physical education - Ginanjar, Shela; Samsudin; Resmana, Dadan; Anugrah, Sendy Mohamad (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background Problems: The proliferation of diverse teaching methodologies underscores the evolving nature of pedagogical practices. Despite this trend, conventional instructional models persist in physical education and health curricula, with many educators continuing to employ traditional approaches. These conventional models limit student engagement and foster a sense of monotony within the learning environment. Conversely, effective physical education hinges on interactive communication, wherein student involvement and enjoyment serve as catalysts for positive motivation and enhanced learning outcomes. Research Objectives: The research aims to determine the enjoyment of students learning physical education using the project-based learning model. Methods: The experimental method was applied with a randomised control-group pretest-posttest design. The population consisted of 600 students from a junior school in Bandung City. The sample was selected using the simple random sampling technique. The enjoyment of student learning questionnaire, which has a reliability value of 0.942. Data were analysed for normality using the Kolmogorov-Smirnov test and homogeneity using the Levene test; after that, the paired test and independent sample t test were carried out. Findings/Results: The result shows that the project-based learning model provides a better influence than conventional learning, especially in the enjoyment of learning aspect, with t = 17.622 and sig = 0.000. Conclusion: The conclusions of this study indicate that employing a project-based learning paradigm centered on fostering enjoyment in the learning process represents a novel advancement in physical education curricula. Emphasising the role of enjoyment in learning, the project-based learning framework offers a fresh perspective on physical education programmes, enabling educators to facilitate more impactful instructional experiences compared to conventional methodologies.